Effects of chard (Beta vulgaris L. Var. Cicla) extract on oxidative injury in the aorta and heart of streptozotocin-diabetic rats - ŞENER, GÖKSEL (My University, 2002)
In diabetes mellitus, increased free radical formation raises the incidence of atherosclerosis and cardiovascular diseases. Regardless of the type of diabetes, the objective of the therapy is to achieve normoglycemia and to prevent or delay the complications. Chard (Beta vulgaris L. var. cicla) is used as a hypoglycemic agent by diabetic patients in Turkey. The aim of this study was to investigate the effect of feeding chard on diabetes-induced free radical-mediated injury in rat aorta and heart tissues. Female Swiss albino rats were randomly divided into four groups: control, diabetic, chard, and diabetic + chard. Rats were subjected to intraperitoneal streptozotocin (STZ, 65 mg/kg) to induce diabetes. Chard extract (2 g/kg) was given for 28 days beginning on the 14th day of the study. Aorta and heart tissue lipid peroxidation and glutathione levels as well as blood glucose levels were determined. The results of the present study indicate that lipid peroxidation was increased and glutathione levels were decreased in both aorta and heart tissue of the diabetic rats. However, treatment with chard extract reversed the effects of diabetes on blood glucose and tissue lipid peroxidation and glutathione levels.